The effect of salinomycin and lasalocid on laboratory cultures of Enterococcus faecium and Staphylococcus gallinarum strains - Lauková, A; Baran, M; Kalacnjuk, G I (Folia microbiologica, 1995)
The growth of Enterococcus faecium strains CCM 4231 and EF 26, and Staphylococcus gallinarum SG 31 was inhibited by salinomycin and lasalocid at concentrations of 25 and 50 mg/L. Staphylococcus gallinarum was more sensitive to the additives used than were enterococci. Maximum inhibition (90%) was measured after the growth with the SG 31 strain in the presence of both ionophores. Growth of organisms was more inhibited by salinomycin at 25 mg/L (67.5%) than at 50 mg/L (63%). The inhibitory effect in enterococcal strains reached after the addition of salinomycin and lasalocid (on average) 63 and 58%, respectively. The CCM 4231 strain was more inhibited by salinomycin as well as by lasalocid than was the EF 26 strain.
Keywords: ionofory; Ionophores; Staphylococcus; Lasalocid; Pyrans; pyrany; Enterococcus faecium; lasalocid